Plant Endophytic Fungus Extract ZNC Improved Potato Immunity, Yield, and Quality - Cao, Juan; Liu, Baoyou; Xu, Xinning; Zhang, Xiaoying; Zhu, Changxiang; Li, Yang; Ding, Xinhua (Frontiers in Plant Science, 2021)
Endophytic fungi play an important role in plant survival and reproduction, but the role of their metabolites in plant growth and immunity, as well as in crop quality formation, is poorly understood. ZNC is a crude ethanol extract from the endophytic fungus Paecilomyces vannayi, and previous studies have shown that it can improve the growth and immunity in Arabidopsis thaliana. The aim of the study was to reveal the trade-off balance between plant growth and immunity by evaluating the mechanisms of ZNC on potato growth, yield, and priming immunity against the oomycete Phytophthora infestans in the indoor and field. The results showed that ZNC maintained a good balance between plant growth and resistance against P. infestans with a high activity. It induced ROS production, promoted plant growth, yield and quality parameters, enhanced the expression of IAA-related genes, and increased the absorption of N. Moreover, the flg22 and chitin signaling pathways contributed to the ZNC-mediated defense response. Two years of field trials have shown that Irrigation with ZNC at one of two optimal concentrations of 1 or 10 ng/ml could significantly increase output by 18.83% or more. The quality of potato tubers was also greatly improved, in which the contents of vitamin C, protein and starch were significantly increased, especially the sugar content was increased by 125%. Spray application of ZNC onto potato plants significantly reduced the occurrence of potato blight disease, showed promising efficacy to 66.49% and greatly increased potato yield in the field. In summary, ZNC, which is a new active plant inducer, is a kind of green trace agricultural input with high efficiency and low cost that has excellent potential in agricultural applications.